Management of Adenovirus in Children after Allogeneic Hematopoietic Stem Cell Transplantation - WY Ip, Winnie; Qasim, Waseem (Advances in Hematology, 2013)
Adenovirus (ADV) can cause significant morbidity and mortality in children following haematopoietic stem cell transplantation (HSCT), with an incidence of up to 27% and notable associated morbidity and mortality. T-cell depleted grafts and severe lymphopenia are major risk factors for the development of adenovirus disease after HSCT. Current antiviral treatments are at best virostatic and may have significant side effects. Adoptive transfer of donor-derived virus-specific T cells has been shown to be an effective strategy for the prevention and treatment of ADV infection after HSCT. Here we review progress in the field and present a pathway for the management of adenovirus in the posttransplant setting.